If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + 4p + p = 0 Combine like terms: p + 4p = 5p 5p + p = 0 Combine like terms: 5p + p = 6p 6p = 0 Solving 6p = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Divide each side by '6'. p = 0 Simplifying p = 0
| 11/29= | | 2=2/m−7 | | 14(7x+14)+3=12(8x+20)+1 | | 188-6x=38 | | 22+5y-5=17y-13-2y | | 2+4x+35-7x=31 | | 2y+1=y+1 | | 6y+2+3y+5=11y-1 | | 16-4x=3x-6 | | C^2-15c-44= | | 10k=8/4 | | -1x^2+11x=27 | | 17=x-32 | | X+6=10x-30 | | 2x-(x+3)=19 | | 60+40+83+x=180 | | 7x+6x^2=20 | | 8+6+35-7x=41 | | n-3n-6n= | | 6y+2+3y+5= | | 5=35s | | 5=35h | | 121m^2-144p^2= | | 36g^2-49h^2= | | -29x/14-23 | | (3n+1)(n+4)=0 | | 12(8x-25)=5(16x+40)-20 | | -3z-2z=10 | | (3XY^2+8)(8-3XY^2)= | | -3z+-2z=10 | | Y-4x+6=0 | | 9e+7=88 |